Vegetation–environment interactions: plant species distribution and community assembly in mixed coniferous forests of Northwestern Himalayas - Rahman, Inayat Ur; Hart, Robbie E.; Afzal, Aftab; Iqbal, Zafar; Bussmann, Rainer W.; Ijaz, Farhana; Khan, Muazzam Ali; Ali, Hamid; Rahman, Siddiq Ur; Hashem, Abeer; Abd-Allah, Elsayed Fathi; Sher, Ali; et al. (Scientific reports, 2023)
One of the main goals of ecological studies is to disentangle the dynamics that underlie the spatiotemporal distribution of biodiversity and further functions of the ecosystem. However, due to many ecological and geopolitical reasons, many remote areas with high plant species diversity have not been assessed using newly based analytical approaches for vegetation characterization. Here, we classified and characterized different vegetation types (i.e., major plant communities) based on indicator species and on the influence of different environmental gradients in the Himalayan mixed coniferous forest, Pakistan. For that, we addressed the following questions: Does the vegetation composition of the Himalayan mixed coniferous forest correlate with climatic, topographic, geographic, and edaphic variables? Is it possible to identify plant communities through indicator species in relation to environmental gradients using multivariate approaches? Can this multivariate be helpful for conservation planning? During four consecutive years we assessed the vegetation composition and environmental variables (21 variables divided in geographic, climatic, topographic, and edaphic groups) of 156 50 m-trasects between an elevation of 2000–4000 m. Using newly based analytical approaches for community characterization, we found a total of 218 plant species clustered into four plant communities with the influence of environmental gradients. The highest index of similarity was recorded between Pinus-Cedrus-Viburnum (PCV) and Viburnum-Pinus-Abies (VPA) communities, and the highest index of dissimilarity was recorded between PCV and Abies-Juniperus-Picea (AJP) communities. Among these four communities, highest number of plant species (156 species) was recorded in PCV, maximum alpha diversity (H’ = 3.68) was reported in VPA, highest Simpson index (0.961) and Pielou’s evenness (0.862) were reported in VPA and AJP. The edaphic gradients (i.e., organic matter, phosphorous, pH and soil texture) and climatic factors (temperature, humidity) were the strongest environmental gradients that were responsible for structuring and hosting the diverse plant communities in mixed coniferous forest. Finally, the Himalayan mixed coniferous structure is more influenced by the spatial turnover beta-diversity process (βsim) than by the species loss (nestedness-resultant, βsne). Our analysis of the vegetation structure along the environmental gradient in the Himalayan mixed coniferous forest supported by sophisticated analytical approaches reveled indicator species groups, which are associated to specific microclimatic zones (i.e., vegetation communities). Within this focus, we side with the view that these results can support conservation planning and management for similar and different areas providing mitigating and preventive measures to reduce potential negative impacts, such as anthropic and climatic.